SOCIAL EMOTIONAL DEVELOPMENT OF SIXTH GRADE STUDENTS DURING LEARNING INTERACTIONS IN AN ELEMENTARY SCHOOL - Desveliksa, Nikeisha Nauri; Dewi, Feti Kumala; Rahmawati, Intan Dyah (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Social emotional development is an important aspect of the learning process in elementary schools because it influences students' ability to interact with others, regulate their emotions, and participate effectively in learning activities. Objectives: This study aimed to describe the social-emotional development of sixth-grade students in the context of learning interactions at State Elementary School 1 Toyareka. Methods: This study employed a quantitative approach with a descriptive research design. The study participants consisted of 51 sixth-grade students. Data were collected using a social-emotional development questionnaire covering six dimensions: self-awareness and emotional security, emotional regulation skills, the need for social support and attachment, empathy and social concern, independence and responsibility, and student–teacher relationships. Data were analyzed descriptively using mean, standard deviation, median, and categorical assessment scores. Results: The results indicated that the overall social-emotional development of sixth-grade students was categorized as good, with a mean score of 74.55. The dimensions of student–teacher relationships and the need for social support and attachment demonstrated the highest achievement levels. Meanwhile, the dimensions of self-awareness, emotional regulation, and empathy were categorized as moderate, with a tendency toward good performance. Conclusions: In conclusion, supportive learning interactions and positive teacher–student relationships are essential factors in promoting the social-emotional development of elementary school students. Therefore, creating a positive and supportive classroom environment should be prioritized to enhance students' social and emotional competencies.